Revisiting the Ranson score in acute pancreatitis: Is the drop in hematocrit a worrisome sign?. (28th June 2022) - Acehan, Fatih; Tez, Mesut; Kalkan, Cagdas; Akdogan, Meral; Altiparmak, Emin; Doganay, Mutlu; Surel, Aziz Ahmet; Ates, Ihsan
Abstract: Background: The Ranson score has 11 parameters that are complex and laborious to implement. In this study, we aimed to create a revised Ranson score by modifying the parameters in Ranson. Methods: A total of 938 patients diagnosed with acute pancreatitis (AP) between 2014 and 2021 were included in the study. The parameters of the Ranson score were included in the univariate and multivariate analyses. According to the results, some of these parameters were modified, and then the revised Ranson score was created. Results: The revised Ranson system was created with nine parameters by modifying the hematocrit parameter at 48 hours and excluding the aspartate aminotransferase parameter from the scoring system. For in‐hospital mortality, the area under the curve value of the revised Ranson was 0.959 (95% CI: 0.931–0.986), and it was significantly higher compared to the three scoring systems evaluated. At a cut‐off value of 3.5, the revised Ranson had a sensitivity and specificity of 91.7% and 89.1%, respectively, for mortality. Conclusion: The revised Ranson scoring system had better predictive ability for all clinical outcomes compared to the original Ranson in our large sample of 938 patients. However, the revised version should be further validated by prospective and multicenter studies.